Ritual Dongkodan Pembentukan Pola Pikir Masyarakat Bajo Gurapin Kabupaten Halmahera Selatan - Idrus Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research on the traditional rituals of Dongko, aims to find out the history of its birth, nonverbal meanings, and the formation of the mindset of the Bajo Guraping Tribe, Kayoa District, South Halmahera Regency. The method used in this study is the conversational engagement method, where researchers can involve themselves directly in activities by observing, listening, and conversing directly with cultural figures and people involved in rituals. The Dongko ritual is a transformation of the story of Princess Datu. The missing Dongko is equipped with offerings that have nonverbal meaning. The Dongko ritual also functions to form a community mindset that is full of communication ethics, social solidarity relationships, and high spiritual awareness